2020
DOI: 10.1177/0300060520971488
|View full text |Cite
|
Sign up to set email alerts
|

Sinonasal teratocarcinosarcoma: a case report and literature review

Abstract: Background Sinonasal teratocarcinosarcoma (SNTCS) is a highly invasive malignant tumor most frequently found in the nasal cavity and paranasal sinuses. As a result, it can be confused with other sinonasal tumors. In addition, SNTCS progresses rapidly and often infiltrates other tissues or organs in the early phase, resulting in poor patient prognosis. The objective of this article was to report the case of a patient with SNTCS and discuss the management strategy. Furthermore, we conducted a literature review f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…They found that the primary treatments used in those patients were surgical resection (87.2%), radiation therapy (59.3%) and chemotherapy (18.6%). 7 The main treatment option is surgery, with negative margins. However, due to the anatomical complexity of the nasal sinuses, surgery does not always achieve complete tumour resection with negative margins; as such, neoadjuvant chemoradiotherapy plus surgical resection is the recommended therapy, with a nearly 88% survival rate after an average of 32 months, as compared with patients treated with surgery and radiation only, who had a 56.5% survival rate at 45 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that the primary treatments used in those patients were surgical resection (87.2%), radiation therapy (59.3%) and chemotherapy (18.6%). 7 The main treatment option is surgery, with negative margins. However, due to the anatomical complexity of the nasal sinuses, surgery does not always achieve complete tumour resection with negative margins; as such, neoadjuvant chemoradiotherapy plus surgical resection is the recommended therapy, with a nearly 88% survival rate after an average of 32 months, as compared with patients treated with surgery and radiation only, who had a 56.5% survival rate at 45 months.…”
Section: Discussionmentioning
confidence: 99%
“…It included 107 SNTCS cases (from 1968 to 2020). They found that the primary treatments used in those patients were surgical resection (87.2%), radiation therapy (59.3%) and chemotherapy (18.6%) 7. The main treatment option is surgery, with negative margins.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] It shows a striking male predominance (approximately 83% of patients) with a male-to-female ratio of 7:1. [6][7][8] The most common site of involvement is the superior aspect of the nasal cavity (approximately 79% of cases) with a predominance of the left side, followed by, in decreasing order of frequency, the paranasal sinuses, orbit, nasopharynx, pharyngeal wall, skull base, cribriform plate, and anterior cranial fossa. 1,6,7,[9][10][11] Nevertheless, rapid growth and extensive local destruction with direct extension into adjacent structures are frequently encountered at the time of diagnosis, and the site of origin cannot be determined in some cases.…”
Section: Epidemiology and Clinical Manifestationsmentioning
confidence: 99%
“…[6][7][8] The most common site of involvement is the superior aspect of the nasal cavity (approximately 79% of cases) with a predominance of the left side, followed by, in decreasing order of frequency, the paranasal sinuses, orbit, nasopharynx, pharyngeal wall, skull base, cribriform plate, and anterior cranial fossa. 1,6,7,[9][10][11] Nevertheless, rapid growth and extensive local destruction with direct extension into adjacent structures are frequently encountered at the time of diagnosis, and the site of origin cannot be determined in some cases. 1,6 Although TCS shows a predilection for the sinonasal tract, in rare cases, tumors showing features resemble TCS have been reported to arise primarily in the thyroid gland and oral cavity.…”
Section: Epidemiology and Clinical Manifestationsmentioning
confidence: 99%
“…Inadequate sampling may lead to erroneous diagnoses of olfactory neuroblastoma, squamous cell carcinoma, undifferentiated carcinoma, adenocarcinoma, malignant salivary gland–type tumours and adenosquamous carcinoma. 5 , 8 …”
Section: Introductionmentioning
confidence: 99%